Conversion of methanol to propylene over nano-sized ZSM-5 zeolite aggregates synthesized by a modified seed-induced method with CTAB. Issue 80 (12th August 2016) - Chen, Hengbao; Wang, Yaquan; Meng, Fanjun; Li, Hongyao; Wang, Shougui; Sun, Chao; Wang, Shuhai; Wang, Xiao
Abstract : Nano-sized ZSM-5 zeolite aggregates with mesopores and high catalytic activity were prepared by a modified seed-induced method using silicate-1 as seeds without additional templates in the presence of a trace amount of CTAB. Abstract : A facile and economical route to synthesize nano-sized ZSM-5 zeolite aggregates with mesopores was developed by a modified seed-induced method using silicate-1 (S-1) as seeds without additional templates in the presence of a trace amount of cetyltrimethylammonium bromide (CTAB). The effect of the amounts of CTAB and S-1 on the morphologies and textural properties were studied in detail, and the possible formation mechanism was proposed. The primary crystal sizes of the ZSM-5 zeolites could be adjusted and mesopores were generated in a certain range. The resulting ZSM-5 zeolites showed a uniformly conglobate morphology with particle sizes of 400–600 nm, aggregated with 20–50 nm crystallites, possessing a large external surface area and abundant inter-crystallite mesopores under the optimum synthesis conditions (CTAB to total SiO2 molar ratio was 0.02 and SiO2 in S-1 gel took up 8% to the total SiO2 ). The catalytic performance of nano-sized ZSM-5 zeolites in methanol to propylene reaction showed a high stability and high propylene selectivity.